Evaluating the Impact of Spinach Supplementation in Enhancing the Growth of Blue Swimming Crab Larvae, Portunus pelagicus - Alias Redzuari; Ariffin Hidir; Muyassar H. Abualreesh; Hanafiah Fazhan; Khor Waiho; Hongyu Ma; Mhd Ikhwanuddin (Tropical Life Sciences Research, 2026)
Blue swimming crabs (Portunus pelagicus) consistently command higher prices in domestic and global markets due to elevated demand. Due to the rising issue of low crab larvae survival, farmers have begun using artificial hormones to increase survival rates and ensure hatchery production aligns with market demands. However, the outcomes of using artificial hormones are concerning, as these compounds pose serious risks to aquatic organisms, humans, and the environment. To address the harmful effects of artificial hormones, efforts are now focused on identifying affordable and eco-friendly plant-based alternatives, such as spinach (Spinacia oleracea), which contains bioactive compounds that could promote crab larval growth and survival. This study aimed to investigate the efficacy of spinach in improving the growth performance of P. pelagicus larvae. This was accomplished by enriching Artemia with spinach, allowing it to serve as a nutrient-enhanced live feed. Compounds in the spinach leaf were extracted with methanol and analysed through GC-MS to identify potential growth-related compounds. LC50 analysis (1,000 ppm–2,000 ppm) was conducted on Artemia to determine the optimal enrichment concentration (1,600 ppm) before use in larval feeding. Results indicated spinach contains compounds such as steroids (5.9%), palmitic acid (5.2%), oleic acid (2.5%) and flavonoids (3.6%) that can potentially improve larval growth. Toxicity analysis showed that the 1,600 ppm treatment was the LC50, meaning it is the optimal concentration for Artemia enrichment, delivering the highest amount of bioactive compounds without affecting Artemia survival. Larvae were fed spinach-enriched Artemia (1,600 ppm) and compared with unenriched Artemia (control). The 1,600 ppm treatment resulted in significantly higher survival at various larval stages (Z1–Z2: 82.6%, Z2–Z3: 91.9%, M–C1: 38.1%), shorter intermoult periods for Z2–Z3 (2.9 days), Z3–Z4 (3.1 days), and M–C1 (3.8 days) and higher SGR (M: 22.5% day⁻¹, C1: 24.5% day⁻¹). Larval steroid analysis supported these findings, with treatment 1,600 ppm yielding higher steroid levels across all stages (511.63–3953 pg/mL), suggesting that spinach-derived steroids may stimulate moulting and enhance larval growth and survival.